JUMPSTART pilot: assessing the acceptability and feasibility of a novel early mobilization program following transcatheter aortic valve replacement - Corovic, Marija; Mosleh, Karen; Karia, Esha; Chan, Sachi; Puglisi, Olivia; Crawshaw, Jacob; Asif, Tasmiya; Sheth, Tej; Velianou, James; Magloire, Patrick; Schwalm, J. D.; Natarajan, Madhu (Frontiers in Cardiovascular Medicine, 2025)
Patients undergoing a transcatheter aortic valve replacement (TAVR) are typically discharged from hospital the next day, leaving little time to support mobilization needs. The JUMPSTART program was developed as a self-directed, tailored and virtual exercise program to improve post-TAVR patients' mobilization. This pilot evaluation assessed the acceptability and feasibility of the preliminary exercise module developed for the program. The evaluation was conducted at a regional cardiac centre in Ontario, Canada. Patients meeting inclusion criteria were contacted via telephone post-discharge and provided with an electronic link to the JUMPSTART exercise module. A second call was made, 14 days post-discharge, to gather feedback regarding module acceptability and feasibility, and to discuss barriers to participation, via a structured survey. Out of the 165 eligible patients who answered the phone when called post-discharge, 112 (68%) completed the survey. A major barrier to participating in the survey evaluation was the technological requirement. Sixty-eight respondents (61%) had done the recommended exercises; they were satisfied with the module (mean = 5.92; 1 = very dissatisfied and 7 = very satisfied) and most rated the exercises as being the “right level of difficulty” (56%). For the 44/112 (39%) who did not try the exercises, key barriers were being busy (n = 13), not feeling well (n = 10), and believing the module was unnecessary (n = 8). The preliminary JUMPSTART module was determined to be acceptable and feasible by TAVR patients who attempted the exercises. Findings refined the implementation of the JUMPSTART program, which has been expanded to include additional modules and is undergoing a comprehensive program evaluation.